Comparison of alpha-2 agonist versus alpha-1 antagonist for post-traumatic stress disorder-associated nightmares in pediatric patients - Seher Khalid, PharmD; Sandra Mitchell, PharmD, BCPP; Cheryl Al-Mateen, MD, FAACAP, DFAPA (American Association of Psychiatric Pharmacists, 2024)
Introduction Posttraumatic stress disorder (PTSD) in children and adolescents has a high prevalence of accompanying sleep disturbances. Currently, pediatric treatment of PTSD-related nightmares is extrapolated from adult studies. This study aims to determine the effectiveness and safety of clonidine and guanfacine compared with prazosin for the treatment of PTSD-related nightmares. Methods This was a retrospective, single-center, medical record review of patients 5 to 17 years old admitted to an inpatient psychiatric unit from January 2015 to September 2021. Patients with a new initiation of an alpha-2 agonist (clonidine or guanfacine) or an alpha-1 antagonist (prazosin) with a diagnosis of PTSD, other trauma- or stressor-related disorder or unspecified anxiety disorder were included. The primary endpoint was the percentage of patients with a decrease in the frequency of nightmares. Results A total of 59 patients were included in the study: 37 in the alpha-2 agonist group and 22 in the alpha-1 antagonist group. There was no statistically significant difference in reduction of nightmares with both groups having a high percentage of patients showing response (alpha-2 agonist: 91.9%, alpha-1 antagonist: 86.4%). Time to decrease in nightmares was comparable between groups with a relatively quick onset. Within the alpha-2 agonist group, clonidine (1.59 ± 1.06 days) compared with guanfacine (3.18 ± 1.74 days) had a statistically significant faster time to reduction in nightmares (p = .005). Discussion Both pharmacologic classes of medications were effective treatment options for pediatric PTSD-associated nightmares with a low incidence of adverse effects. There was a quick time to onset seen with all agents.